Marqueurs épidémiologiques de Pseudomonas aeruginosa: isolament de quatre nouveaux pyocinotypes - Ferreira, Maria Odette Santos (2017)
The pyocing—typing of 418 Ps. aeruginosa from several Hospitais in Lisbonne has been done with the Gillies and Govan method; 69% Portuguese strains are in pyocinotypes nº 1, 3, 5 and 7; 16% are in 24 other pyocinotypes. Four new pyocinotypes were found in a group of 34 atypical strains. The relashionship between serotype and pyocinotype was investigated and the most frequented serotypes in Portugal (0:11; 0:6; 0:3) has been subdivided into numerous pyocinotypes with epidemiological significance.